EFFECT OF LEARNING WITH ABDUCTIVE-DEDUCTIVE STRATEGY TOWARDS THE ACHIEVEMENT OF REASONING ABILITY OF HIGH SCHOOL STUDENTS - Ali Shodikin (IKIP Siliwangi and I-MES, 2017)
The purpose of this study was to investigate the effect of learning with abductive-deductive strategy towards the achievement of mathematical reasoning abilities of high school students. Research carried out an experimental pretest-posttest design and the control group was not randomized in class XI student at one high school in Pati, Central Java, Indonesia. Data analysis was conducted quantitative research based on early mathematical ability categories (KAM) and overall. The results showed that the achievement of mathematical reasoning abilities that students acquire learning abductive-deductive strategy better than students who received the expository learning. In more detail of KAM categories, only middle category that show achievement of mathematical reasoning abilities better. While in upper and under categories have the same reasoning abilities achievements. This research is expected teachers can encourage students to do abduction and deduction in the learning achievement of students’ mathematical reasoning abilities.